A note on the computation of the hamming bound - Abaya, Efren F.
This paper derives a simple approximation to a binomial sum occurring in the Hamming Bound. The approximation is easy to compute and quite accurate, even for modest values of the parameters involved. The approximation permits easy calculation of the minimum number of parity bits required for t error correction.